2005
DOI: 10.1128/aem.71.1.29-38.2005
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of PCR Primers To Assess the Diversity of Clostridium spp. in Cheese by Temporal Temperature Gradient Gel Electrophoresis

Abstract: A nested-PCR temporal temperature gradient gel electrophoresis (TTGE) approach was developed for the detection of bacteria belonging to phylogenetic cluster I of the genus Clostridium (the largest clostridial group, which represents 25% of the currently cultured clostridial species) in cheese suspected of late blowing. Primers were designed based on the 16S rRNA gene sequence, and the specificity was confirmed in PCRs performed with DNAs from cluster I and non-cluster I species as the templates. TTGE profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
1
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 30 publications
1
49
1
7
Order By: Relevance
“…On the basis of 16S rRNA gene sequence analyses, 73 out of 152 validly described species fall within cluster I, often referred to as Clostridium sensu stricto (9,39). Spores of clostridia belonging to cluster I are responsible for spoilage of cheeses with long ripening times, causing the so-called late blowing defect (17,22,38). Specifically, species able to convert lactic acid to butyric acid, carbon dioxide, and hydrogen at relatively low pH are detrimental (22,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of 16S rRNA gene sequence analyses, 73 out of 152 validly described species fall within cluster I, often referred to as Clostridium sensu stricto (9,39). Spores of clostridia belonging to cluster I are responsible for spoilage of cheeses with long ripening times, causing the so-called late blowing defect (17,22,38). Specifically, species able to convert lactic acid to butyric acid, carbon dioxide, and hydrogen at relatively low pH are detrimental (22,38).…”
mentioning
confidence: 99%
“…Spores of clostridia belonging to cluster I are responsible for spoilage of cheeses with long ripening times, causing the so-called late blowing defect (17,22,38). Specifically, species able to convert lactic acid to butyric acid, carbon dioxide, and hydrogen at relatively low pH are detrimental (22,38). Clostridium tyrobutyricum is considered the primary cause of late blowing.…”
mentioning
confidence: 99%
“…In a study of the bacterial community from an artisanal Sicilian cheese, Randazzo et al (2002) compared the intensity of bands from DNA and RNA-derived DGGE profiles and concluded that some species of the samples were not very metabolically active. Other studies of RNA profiles involving either DGGE (Rantsiou et al, 2008b;Dolci et al, 2010;Masoud et al, 2011), TTGE (Le Bourhis et al, 2007), SSCP (Le Bourhis et al, 2005), T-RFLP (Sanchez et al, 2006), clone library sequencing (Carraro et al, 2011) or pyrosequencing (Masoud et al, 2011) have been published.…”
Section: Pcr-based Methods For Microbial Diversity Investigationmentioning
confidence: 99%
“…Denaturing gradient gel electrophoresis (DGGE), temperature gradient gel electrophoresis (TGGE) and temporal temperature gradient gel electrophoresis (TTGE) are widely used to study cheese microbial communities Ercolini et al, 2001;Ogier et al, 2002;Randazzo et al, 2002;Ercolini et al, 2003;Mauriello et al, 2003;Andrighetto et al, 2004;Cocolin et al, 2004;Ercolini et al, 2004;Henri-Dubernet et al, 2004;Lafarge et al, 2004;Ogier et al, 2004;Rantsiou et al, 2004;Le Bourhis et al, 2005;Flórez and Mayo, 2006;Randazzo et al, 2006;Cocolin et al, 2007;El-Baradei et al, 2007;Le Bourhis et al, 2007;Parayre et al, 2007;Abriouel et al, 2008;Bonetta et al, 2008;Ercolini et al, 2008;Gala et al, 2008;Henri-Dubernet et al, 2008;Nikolic et al, 2008;Rantsiou et al, 2008b;Van Hoorde et al, 2008;Alegría et al, 2009;Casalta et al, 2009;Dolci et al, 2009;Giannino et al, 2009;Serhan et al, 2009;Dolci et al, 2010;Fontana et al, 2010;Fuka et al, 2010;Randazzo et al, 2010;Van Hoorde et al, 2010;Masoud et al, 2011). Target sequences from rRNA or housek...…”
Section: Pcr-based Methods For Microbial Diversity Investigationmentioning
confidence: 99%
See 1 more Smart Citation